2015
DOI: 10.1016/j.atherosclerosis.2015.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of NAMPT in PBMC from patients with acute coronary syndrome and in inflammatory M1 macrophages

Abstract: Based on our in vivo and in vitro findings we suggest that NAMPT could contribute to systemic and plaque inflammation in atherosclerotic disorders at least partly through effect on macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 36 publications
0
27
0
2
Order By: Relevance
“…23) In this study; we found that the levels of iNAMPT and eNAMPT secretion were significantly increased in the patients with ACS compared with the normal controls, which was consistent with the findings in patients with coronary artery disease (CAD). 24) The expression levels of NAD+, CRP and IL-6 levels in plasma of ACS patients and SIRT1 level in PBMC were higher than those in the control group, which suggesting that the up-regulation of the NAMPT/NAD+/SIRT1 signaling pathways may contribute to the inflammatory response. A study showed that NAMPT promoted the synthesis of NAD+ and activates the post transcriptional modification of SIRT on TNF molecules and promotes the expression of IL-6.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…23) In this study; we found that the levels of iNAMPT and eNAMPT secretion were significantly increased in the patients with ACS compared with the normal controls, which was consistent with the findings in patients with coronary artery disease (CAD). 24) The expression levels of NAD+, CRP and IL-6 levels in plasma of ACS patients and SIRT1 level in PBMC were higher than those in the control group, which suggesting that the up-regulation of the NAMPT/NAD+/SIRT1 signaling pathways may contribute to the inflammatory response. A study showed that NAMPT promoted the synthesis of NAD+ and activates the post transcriptional modification of SIRT on TNF molecules and promotes the expression of IL-6.…”
Section: Discussionmentioning
confidence: 85%
“…The study showed that the expression of NAMPT was up-regulated in cardiovascular disease patients; 24) however, whether it is useful or harmful is not clear. Study has shown that the down-regulation of NAMPT expression in ApoE knockout mice can promote the reverse cholesterol transport in macrophages through PPARα-LXRα-ABCA1/G1 signaling pathway and has an antiatherosclerotic effect.…”
Section: Discussionmentioning
confidence: 97%
“…Macrophages can also exist in intermediate polarization states and switch phenotype in response to stimuli, for example the macrophage colony-stimulating factor (M-CSF) and granulocytemacrophage colony-stimulating factor (GM-CSF) polarizes monocytes to M2 and M1 macrophages, respectively [162,163]. In paper II, differentiation of primary monocytes towards macrophages was performed using M-CSF for 7 days before stimulation with either interferon (IFN)γ and LPS or interleukin (IL) 4 for M1 or M2 polarization, respectively [163,164].…”
Section: Differentiation Of Macrophagesmentioning
confidence: 99%
“…Verification of macrophage polarization by this protocol has been done previously using mRNA expression of markers like tumor necrosis factor (TNF) and IL-6 for M1 and CD163 and peroxisome proliferator-activated receptor γ for M2 [164]. Primary monocytes have previously been shown not to secrete legumain, whereas M-CSF-differentiation of macrophages resulted in substantial secretion of prolegumain to the conditioned media [36].…”
Section: Differentiation Of Macrophagesmentioning
confidence: 99%
“…Nicotinamide phosphoribosyltransferase (NAMPT) is a crucial enzyme in the cyclic biosynthetic pathway of nicotinamide adenine dinucleotide (NAD), serving as the catalyzer of the generation from nicotinamide (NM) to nicotinamide mononucleotide (NMN) 5 . Indeed, it has been postulated that NAMPT may participate in the regulation of inflammation and is responsible for many inflammatory diseases 6,7 . NAMPT was also involved in the regulation of apoptosis 8‐10 .…”
Section: Introductionmentioning
confidence: 99%